Sistem Pendukung Keputusan Pemilihan Instruktur Bimbingan Belajar Menggunakan Metode PSI (Preference Selection Index) - Fauziyah, Fauziyah; Nugroho, Fifto; Buulolo, Efori (Building of Informatics, Technology and Science (BITS), 2022)
Service activities aim for the long term in creating HR (Human Resources) who have knowledge and creativity in the field of computers, especially in graphic design and multimedia applications. This training aims to train students in using tools in graphic design applications, for example. Corel Draw, so students are expected to know how to plan and develop students' creative abilities in designing. This activity is carried out using the social method of graphic design applications using the Corel Draw application, and an instructor who is an expert in the field of graphic design. to guide the operation of the application, thereby helping trainees in the practice of making designs. Decision support system, is a system that is used to facilitate decision making in selecting a graphic design training instructor, where the decision making process is basically choosing alternative decisions in determining the eligibility of a person to become a design training instructor, the assessment can be seen from several assessment criteria, namely experience, consistent, creative and communicative. In facilitating the selection process, a decision support system is used using the PSI (Preference Selection Index) method to produce the best weights and preferences. So that the final result obtained as a tutoring instructor is alternative A11 on behalf of Sriwulan with the first rank with the highest score of 0.9196